Recent advances in anion exchange membrane technology for water electrolysis: a review of progress and challenges - Abdul Qayoom; Muhammad Shakeel Ahmad; H. Fayaz; Atika Qazi; Jeyraj Selvaraj; Rahadian Zainul; Krismadinata; Nasrudin Abd Rahim; Farruh Atamurotov; Thien Khanh Tran; Basma Souayeh; Natei Ermias Benti (Energy Science & Engineering)
Abstract Clean energy and environmental pollution are two key concerns of modern society and are pivotal necessities for the economic, social, and sustainable development of the world. Today around 80% of energy is generated using nonrenewable resources and fossil fuels (oil, gas, coal) which ultimately results in hazardous global emissions. As a clean substitute for fossil fuels, hydrogen has emerged as a promising and renewable energy resource. Utilization of this energy resource requires the development of active, stable, low‐cost environmentally friendly techniques. Water splitting electrolysis is a method for producing clean and efficient hydrogen using an environmentally benign technique that is currently at its most mature stage. Electrolysis is attracting ever‐increasing attention, as it is a promising electrochemical device for hydrogen production from water due to the high conversion efficiency and relatively low energy input required when compared to thermochemical and photocatalytic methods. This paper will outline the need, performance, and insight of anion exchange membrane (AEM) electrolyzer. Recent developments in the design and preparation of AEM. New strategies for activity, stability, and efficiency improvement of AEM. Membrane types, and factors affecting AEM performance in an electrolyzer. This review also discusses the effects, operating characteristics, and energy consumption of electrocatalysts in the AEM electrolyzer. Hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) pathways and mechanisms in acidic and alkaline media. This study seeks to provide a detailed overview of recent accomplishments in the field of the hydrogen economy, particularly electrolysis, to inspire further research and development to address the technology's obstacles.